Pengaruh Financial distress, Perencanaan Pajak, dan Kualitas Audit Terhadap Manajemen Laba (Studi Kasus Pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2016-2020) - Melinda, Rayi Hana; Hapsari, Dini Wahjoe; Farida, Ajeng Luthfiyatul (eProceedings of Management, 2023)
Profit is one of the information in the financial statements that can be used by the public in making investmentdecisions. The motivation of management to practice earnings management is to attract external parties, one of whichis investors by increasing profits (income creating) and tax motivation by decreasing profits (income decreasing).This study aims to determine the effect of financial distress, tax planning, audit quality on earnings management inmining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period simultaneously orpartially. The data used in this study were obtained from annual reports and audited financial statements for 2016-2020. The population in this study are mining sector companies listed on the Indonesia Stock Exchange (IDX) for the2016-2020 period. The sample used was purposive sampling from 29 samples with a total of 145 observational data.The analysis used in this study uses panel data regression analysis. The results showed that financial distress, taxplanning, audit quality had a simultaneous effect on earnings management. The partial test results show that financialdistress has a positive effect on earnings management, while tax planning and audit quality have no effect on earningsmanagement.Keywords-audit quality, earnings management, financial distress, tax planning